An applied phenomenology: the inner life of writing poetry with street photography. - Tay, Eddie (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2024)
This paper discusses how phenomenology contributes to an understanding of the processes of writing poetry with street photography set in Hong Kong and Singapore. It looks at distinctions between pure phenomenology as academic exegetical and critical debates and applied phenomenology as a form of attentional practice. It then argues that applied phenomenology offers a refined critical vocabulary for describing the creative practices, hence constituting an inner life of writing that informs life writing. By looking at the author's own writing and street photography practices, it then discusses the relevance of applied phenomenology for an understanding of the creative practices in relation to everyday life in the hypercapitalist cities of Singapore and Hong Kong. In this way, the reflexive situation of the creative self is shown to be aligned with phenomenological practice.